Analysis of episiotomy incidence and risk factors in vaginal deliveries: a single-centerAJOG Global Reports at a Glance - Suskhan Djusad, MD, PhD; Intan Indah Permatasari, MD; Annisa Futihandayani, MD; Puti Shahnaz, MD; Daniel Hadiwinata, MD; Hana Fathia Herianti, MD (Elsevier, 2024)
Introduction: Episiotomy is a surgical procedure involving the enlargement of the posterior vagina to facilitate the delivery of the baby. This study aims to further investigate the associated risk factors for episiotomy and the specific indications for its use in spontaneous labor. Methodology: This institutional-based cross-sectional study was conducted among 349 vaginal births with a ratio of 1:4 from January 2020 to December 2020. We recruited study participants using consecutive sampling techniques. The sample size was calculated with a hypothesis test for two population proportions (one-sided test formula). Adjusted odds ratio with the corresponding 95% confidence interval was used to declare the significance of variables. Results: In our multivariate analysis, it was found that pregnant women who underwent instrumental delivery (P-value=.00; OR=25.63; 95% CI: 5.76-114.0) and those with fetal birth weight >3,000 grams (P-value=.00; OR=11.31; 95% CI: 3.96-32.32) had the highest risk of undergoing an episiotomy. Subsequently, the duration of the second stage of labor >30 minutes (P-value=.049; OR=16.34; 95% CI: 1.01-264.48) was associated with a slightly increased risk of episiotomy. Fetal head circumference >34 cm was not found to be risk of an increased risk of episiotomy in this study. However, pregnant women aged >30 years (P-value=.049; OR=0.306; 95% CI: 0.94-0.99) showed a reduced risk of episiotomy. Conclusion: The prevalence of episiotomy practice in this study exceeds the recommended threshold set by the World Health Organization (WHO). Instrumental delivery, high birth weight, and prolonged second-stage labor emerged as significant factors influencing episiotomy practice. Hence, further interventions are warranted to mitigate the prevalence of episiotomy practice.